Clima organizacional y satisfacción laboral del personal de enfermería en el área de nefrología del hospital nacional, Lima 2024 - Ilave Aguirre, Dora Ada (2025)
Introduction: Currently, the country's government entities need to optimize the work environment, since according to the World Health Organization (WHO), the culture of organizations directly impacts job satisfaction and staff preferences when choosing their employer, influencing primary care in patient care regardless of whether they belong to a Clinic or a Hospital, leaving aside their vocation. In this context, these public entities can improve job satisfaction, the result being organizational management. Objective: "To establish the existing correlation between the organizational climate and job satisfaction of nursing staff in the Nephrology area of the National Hospital, Lima 2024." Method: The analysis of the study will be quantitative, applied, cross-sectional, and correlational. For this purpose, the representative sample will consider 116 nursing graduates and 44 technicians, who work in the Nephrology area. The Organizational Climate Questionnaire developed by Salas (Lima, 2020) and the Job Satisfaction Questionnaire adapted by Canevaro (Lima, 2020) will be applied, both being Likert-type instruments. On the other hand, for data processing and generation of graphs and tables, IBM SPSS STATISTICS Version 25 software will be used, and the hypothesis will be tested with Spearman's statistical test.